Intertissue mechanical interactions shape the olfactory circuit in zebrafish. (9th December 2021) - Monnot, Pauline; Gangatharan, Girisaran; Baraban, Marion; Pottin, Karen; Cabrera, Melody; Bonnet, Isabelle; Breau, Marie Anne
Abstract: While the chemical signals guiding neuronal migration and axon elongation have been extensively studied, the influence of mechanical cues on these processes remains poorly studied in vivo . Here, we investigate how mechanical forces exerted by surrounding tissues steer neuronal movements and axon extension during the morphogenesis of the olfactory placode in zebrafish. We mainly focus on the mechanical contribution of the adjacent eye tissue, which develops underneath the placode through extensive evagination and invagination movements. Using quantitative analysis of cell movements and biomechanical manipulations, we show that the developing eye exerts lateral traction forces on the olfactory placode through extracellular matrix, mediating proper morphogenetic movements and axon extension within the placode. Our data shed new light on the key participation of intertissue mechanical interactions in the sculpting of neuronal circuits. Synopsis: In zebrafish embryos, eye morphogenesis steers neuronal movements and axon extension in the overlying olfactory placode by exerting traction forces in the lateral direction, transmitted to the placode through extracellular matrix. The cell bodies of olfactory placode neurons and cells in the adjacent eye tissue undergo highly correlated morphogenetic movements in the mediolateral direction, suggesting an interaction between the two tissues. In mutants lacking eyes, mechanical stress at the lateral border of the placode and lateral movements of olfactory placode neurons is reduced, resulting in thinner placodes and shorter axons. Enzymatic degradation of the extracellular matrix perturbs cell movements in the placode and decreases their correlation with eye cell movements, providing evidence that the matrix mechanically couples the two tissues. Abstract : In zebrafish embryos, eye morphogenesis steers neuronal movements and axon extension in the overlying olfactory placode by exerting traction forces in the lateral direction, transmitted to the placode through extracellular matrix.